2009
DOI: 10.1097/pas.0b013e3181a9cd6c
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Epithelioid Cell Tumor With SFPQ/PSF-TFE3 Gene Fusion in a Patient With Advanced Neuroblastoma

Abstract: We report a case of perivascular epithelioid cell tumor (PEComa) with an SFPQ/PSF-TFE3 gene fusion in a 14-year-old girl treated for adrenal neuroblastoma for 4 years. Imaging studies revealed a tumor in the wall of the sigmoid colon, which was radiologically different from the neuroblastoma, together with several inguinal and cervical lymph node metastases of the neuroblastoma. Microscopically, the tumor in the sigmoid colon showed sheet-like growth of epithelioid cells with abundant clear cytoplasm and round… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 21 publications
2
57
0
Order By: Relevance
“…In fact, 9 different types of tumors with TFE3 immunoreactivity are known [8,9]. Strong TFE3 immunoreactivity has been reported in a subset of perivascular epithelioid cell tumor and RCCs due to genetic alterations involving TFE3 [8,10,11,17]. These results indicate that TFE3-positive findings do not always lead to a confirmed diagnosis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In fact, 9 different types of tumors with TFE3 immunoreactivity are known [8,9]. Strong TFE3 immunoreactivity has been reported in a subset of perivascular epithelioid cell tumor and RCCs due to genetic alterations involving TFE3 [8,10,11,17]. These results indicate that TFE3-positive findings do not always lead to a confirmed diagnosis.…”
Section: Discussionmentioning
confidence: 75%
“…TFE3 immunoreactivity is highly sensitive and specific for ASPS; however, this specificity was not mutually exclusive. More recently, in a subset of perivascular epithelioid cell tumor, gene fusion involving the TFE3 gene has been reported [10,11]. Strong immunoreactivities for monocarboxylate transporter 1 and its interacting partner CD147 have been reported for the cytoplasm of ASPS tumor cells.…”
Section: Introductionmentioning
confidence: 96%
“…(5) ASPS are typically negative for "melanocytic" markers (extremely rare exceptions noted). (6) ASPS exhibits t(X;17), whereas PEComa has been found to have a t(X;1) translocation [7][8][9].…”
Section: Discussionmentioning
confidence: 96%
“…27 In addition to alveolar soft part sarcoma and Xp11.2 renal cell carcinoma, rearrangements of TFE3 have also recently been identified in PEComas; TFE3 expression was shown using IHC in five of 17 cases and fusion of PSF/TFE3 was established in one case by RT-PCR and FISH. 54,55 Subsequently, four extra-renal site TFE3-rearranged PEComas were identified that suggested an association with younger age, lack of tuberous sclerosis, and prominent epithelioid cells with alveolar architecture, although fusion with PSF was not detected in the two cases tested. 33 In summary, we have validated a FISH probe set for use in formalin-fixed, paraffin-embedded tissues to detect TFE3 rearrangement with a reflex strategy to identify TFE3/ASPSCR1 fusion.…”
Section: Discussionmentioning
confidence: 99%